Role of TLR4, NLRC1/NOD1 and NF-κB in Inflammation of Gastric Mucosa in Helicobacter pylori Infection in Children - O.Ye. Abaturov; O.M. Gerasymenko (Zaslavsky O.Yu., 2014)
The aim of the work was to study the role of TLR4, NLRC1/NOD1 and NF-κB in inflammation of gastric mucosa (GM) in children with chronic inflammatory H.pylori-associated gastroduodenal diseases of the intestinal tract. Methods. We observed 128 children with chronic gastroduodenal diseases in the acute stage: 70 (54.7 %) children (mean age 14.04 ± 0.34 years) infected with H.pylori, and 58 (45.3 %) - in which H.pylori was not detected (mean age 14.12 ± 0.43 years). We used molecular genetic methods to determine the level of TLR4, NLRC1/NOD1 expression if biopsy material of GM and NF-κB in peripheral blood lymphocytes. Results. It is shown that patients infected with H.pylori show increased level of both TLR4 gene and NLRC1/NOD1 expression in biopsy material of GM at reducing activity of transcription factor NF-κB expression in lymphocytes, unlike children, whose disease was not associated with H.pylori infection. In children infected with CagA(+)-strains of H.pylori we detected significantly lower activity of expression only of the transcription NF-κB in peripheral blood lymphocytes. We propose a model of participation of non-specific mechanisms of innate immunity in the development of chronic inflammation of the gastric mucosa of gasrtoduodenal part of the intestinal tract in children infected with CagA(+)- and CagA(-)-strains of H.pylori.